Deep learning asan advanced concept of artificial intelligence (Trinity Journal of Management, IT & Media (TJMITM), 2018)
This paper represented on the Deep learning technique growing  in the learning community of machines, as traditional learning  architecture has proven incompetent for the machine learning  challenging tasks and strong feature of artificial intelligence (AI).  Increasing and widespread availability of computing power,  along the use of efficient training and improvement algorithms,  has made it possible to implement, until then, the concept of deep  learning. These development events deep learning architecture  and algorithms look at cognitive neuroscience and point to  biologically inspired solutions for learning. This paper  represented on the rule of Convolutional Neural Networks  (CNNs), Neural Networks (SNNs) and Hierarchical Temporary  Memory (HTM), and other related techniques to the least mature  technique.
Keywords: Neuron Model; Predictive State model; Echo Model; Spike Neural Network